Association between the Analytical Technique and Finite Element Method for designing SPMSMs with Inner Rotor Type for Electric Vehicle Applications - Nguyen, Duc-Quang; Thai, Thanh Nguyen; Thi, Cuc Le; Minh, Dinh Bui; Quoc, Vuong Dang (Engineering, Technology & Applied Science Research, 2024)
This paper focuses on computing the electromagnetic parameters of inner rotor-configuration Surface-mounted Permanent Magnet Synchronous Motors (SPMSMs) via the combination of analytical and finite element methods with an application to electric bicycles. The analytical method is, first, developed in detail to calculate the essential parameters of the inner rotor-configuration SPMSM. Then, a Finite Element Method (FEM) is introduced to verify the analytical parameters found. Further, a simulation of magnetic flux density, torque, cogging torque, torque ripple, back Electromagnetic Force (EMF), linkage flux, and temperature is performed. The end result is validated with a real 2.2 kW inner rotor-configuration SPMSM.